Fifteen-minute consultation: assessment of a child with suspected shunt problems. Issue 4 (10th January 2017) - Mangat, Harpreet Singh; Patel, Chirag; Rodrigues, Desiderio
Abstract : Cerebrospinal fluid diversion procedures have saved more lives than any other neurosurgical procedure. However, they do have a unique set of complications which a paediatrician in a district general hospital may encounter. Timely recognition and appropriate referral to the neurosurgeon is vital in order to avoid serious consequences and to have a favourable outcome.